ANALYSIS OF HOUSEHOLD INCOME STRUCTURE, EXPENDITURE, AND WELFARE LEVEL OF CORN FARMERS IN LAREH SAGO HALABAN SUB-DISTRICT, LIMA PULUH KOTA REGENCY - Silvia Dewita; Faidil Tanjung; Nofialdi Nofialdi (SEAN Institute, 2023)
This study aims to analyze the structure of income, household expenses and the level of welfare of corn farmers in Lareh Sago Halaban District, Fifty City District. The method used is a survey method with a total sample of 60 respondents. Data analysis is descriptive quantitative. The results showed that the average income of large farmers (land area > 1 ha) was Rp. 79,271,571/year, the largest income came from corn farming income, namely 47%. While the average income of medium farmers (land area 0.51-1 Ha) is Rp. 57,605,290,-/year, the biggest contributor to household income is non-corn and non-agricultural income with a respective percentage of 38%, and the average income of smallholder households (land area 0.1-0.5 Ha) is Rp. 50,376,508, -/year, the largest percentage comes from non-agricultural income, namely as much as 66%. The expenditure structure of corn farmer households consists of food expenditures, non-food expenditures and production costs expenditures. The average household expenditure of large, medium and small farmers respectively is Rp. 73,377,904, -/year, Rp. 53,189,260,-/year and Rp. 40,906,654,/year. Overall, the biggest expenditure for farmers is for food needs and the smallest is for production costs. The level of farmer welfare is measured by the income share of the agricultural sector by 72% for farmers with large land areas and 62% for farmers with medium land areas and the rest is income from the non-agricultural sector. Meanwhile, for smallholder farmers, 34% of their income is from the agricultural sector and 66% is income from the non-agricultural sector. The share of expenditure on food for farmer households for all farmer categories is <60%, meaning that corn farming households are included in the food security category. The average NTPRP> 1, it can be concluded that the welfare level of farmers is included in the prosperous group.